Totally Muslim Truly Intellectual-Based Holistic Education in Postgraduate Programs - Yahuda, Robbin Dayyan; Susanto, Roni; Widodo, Wahyu; Syahrudin, Syahrudin; Kolis, Nur (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
This study was motivated by the failure of some formal educational institutions in Indonesia to apply the purpose of holistic Islamic education, resulting in the decadence of students’ morality. The evidence of students’ moral decadence is the high number of inter-student quarrels and the number of extramarital pregnancies in the last 8 years; that number is up 20 percent compared to the previous period. Holistic Islamic education should balance reason, morals, and physical students to produce intelligent graduates. Based on resourceful education, moral education, and physical education, this study discusses the implementation of holistic Islamic education purposes based on totally Muslim and truly intellectual in the IAIN Ponorogo postgraduate program. Using a qualitative approach, this study traces the concept of educational objectives in the IAIN Ponorogo postgraduate program and its implementation of education goals. The research period is limited to 2022, while the total number of informants is seven people. The data analysis uses content analysis methods such as data reduction, display, and conclusion. The data display uses domain analysis. The results of the study show that the three, that is, phase A (dhikr, thinking, and behavior), phase B (multidiscipline and multi-culture), and phase C (nobility, novelty, and solution) of implementations of holistic Islamic education purpose based on totally Muslim truly intellectual in the IAIN Ponorogo postgraduate program -, are relevant to the resourceful education, moral education, and physical education goals.